The throwing shoulder in youth elite handball: adaptions of inferior but not anterior capsule thickness differ between the two sexes - Winkelmann, M. T.; Achenbach, L.; Zeman, F.; Laver, L.; Walter, S. S. (Research in Sports Medicine, 2023)
The aim was to investigate side-to-side and sex differences of anterior and inferior capsule thickness (ACT, ICT) between the throwing and non-throwing shoulder (TS, NTS) in youth elite handball players. 125 youth female and male elite handball players (14.1±0.7yo) were assessed for ACT and ICT by ultrasound . ACT measurement was performed from anterior (3 o`clock) in upright position and for ICT from inferior (6 o`clock) in supine position. Measurements of ICT in the TS of all athletes (1.4±0.2 mm) differed significantly but marginally to those in the NTS (1.3±0.2 mm) (p = 0.001). Female (1.2±0.2 mm vs. 1.3±0.2 mm; p = 0.007) but not male youth players (1.4±0.2 mm vs. 1.4±0.2 mm, p = n.s.) demonstrated slight differences in ICT in the TS compared with the NTS. Although significant, the thickness in the TS compared to the NTS was within the measurement accuracy of the ultrasonic assessment. No difference in ACT was observed in the TS (1.4±0.3 mm) compared to the NTS (1.4±0.3 mm) for both sexes (n.s.).